Medical and health benefits of noise reduction at Intensive Care Units - Krzysztof; Zuzanna Bialkowska; Mateusz Górka; Weronika Stec; Anna Wojtkiewicz; Zuzanna Kudas; Magda Piekarska (Nicolaus Copernicus University in Toruń, 2024)
Introduction: The presence of excessive noise poses a significant risk to the overall well-being and health of individuals. The presence of elevated noise levels within Intensive Care Units (ICUs) has the potential to exert detrimental effects on both the well-being of patients and the healthcare personnel. The aim of this study: This study aims to gather knowledge about the effects of noise pollution on patient's wellbeing within Intensive Care Units, analyze various investigations around the world and discuss the possible preventive methods of reducing noise and thus sleep disturbances. Materials and methods: This review was based on available data collected in the PubMed database and Google Scholar web search engine using the key words Intensive Care Unit, sleep deprivation, noise pollution Conclusions: Intensive Care Unit noise disrupts patient's sleep, communication, and increases stress, potentially leading to medical errors and longer recovery times. Addressing this issue is vital, aligning with patient-centered care and holistic therapy trends. Solutions include architectural changes, quieter equipment, staff education, clinical guidelines, and providing earplugs and eye masks for patient comfort. Noise negatively impacts sleep, causing circadian disruptions, cognitive impairments, and health issues. Identifying and mitigating noise sources can significantly enhance patient well-being and treatment outcomes.